1983
DOI: 10.1097/00004032-198310001-00048
|View full text |Cite
|
Sign up to set email alerts
|

An Update of Epidemiologic Studies of Plutonium Workers

Abstract: Retrospective and prospective epidemiologic studies are being conducted as part of a national survey of plutonium workprs at.follr (le~artment of Energy faciliti~s (Los Alamr)s, NM: Rocky Flats, CO; Wound Laboratory, OH; and Savannah Riv~r, SC). A prelirrinary analysis of mcrtality was di:n~f or all~llli~e maIFS who have workw; at l.hc' ROCkY Flats Plant during th~period 1952 to 1979. The 452 observed depths were significantly fwer than tbc 1131exp~cted for all causes. The 107 draths cllie tc aii n~~ligrlantnr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Results of a few epidemiologic studies have suggested that occupational exposures within the petrochemical industry [ThCriault and Goulet, 1979;Thomas et al, 1982;Waxweiler et al, 19831, vinyl chloride industry [Monson et al, 1974;Waxweiler et al, 19761, and nuclear industry [Voelz et al, 1983;Hadjimichael et al, 1983;Acquavella et al, 19851 increase the risk of developing central nervous system (CNS) cancers. However, other studies have failed to demonstrate such increased risk [Fox and Collier, 1977;Gilbert and Marks, 1979;Rushton and Alderson, 1981;ThCriault and Allard, 1981;Wen et al, 1983;Austin andSchnatter, 1983a and1983b;Reyes et al, 1984;Hanis et al, 1985;Beral et al, 19851. This epidemiologic investigation was a case-control study nested among workcrs employed between 1943 and 1977 at two nuclear facilities located in Oak Ridge, Tennessee.…”
Section: Introductionmentioning
confidence: 99%
“…Results of a few epidemiologic studies have suggested that occupational exposures within the petrochemical industry [ThCriault and Goulet, 1979;Thomas et al, 1982;Waxweiler et al, 19831, vinyl chloride industry [Monson et al, 1974;Waxweiler et al, 19761, and nuclear industry [Voelz et al, 1983;Hadjimichael et al, 1983;Acquavella et al, 19851 increase the risk of developing central nervous system (CNS) cancers. However, other studies have failed to demonstrate such increased risk [Fox and Collier, 1977;Gilbert and Marks, 1979;Rushton and Alderson, 1981;ThCriault and Allard, 1981;Wen et al, 1983;Austin andSchnatter, 1983a and1983b;Reyes et al, 1984;Hanis et al, 1985;Beral et al, 19851. This epidemiologic investigation was a case-control study nested among workcrs employed between 1943 and 1977 at two nuclear facilities located in Oak Ridge, Tennessee.…”
Section: Introductionmentioning
confidence: 99%
“…Only by using restrictive regression analyses could an increased lung cancer rate be shown (Brown et al 2004). Other studies showed a PROFAC for lung cancer mortality in plutonium workers at the Rocky Flats Plant of 0.86 (one observed, seven expected) (Tietjen 1987), and Voelz et al (1983) found a PROFAC 0.80 for lung cancer in these plutonium workers. Manhattan Project plutonium workers had a median internal dose of 1.25 Sv and in all causes of death a PROFAC of 0.57 compared to the general population; their PROFAC for lung cancer was 0.32 (Voelz et al 1997).…”
Section: Low-level Background Radiation and Hormesismentioning
confidence: 94%
“…The original study (Voelz et al, 1983) extracted the job histories of 25 percent of the cohort. Although no computer file containing that information was located, a printed version was.…”
Section: Development Of Job Information and A Job Dictionarymentioning
confidence: 99%
“…The initial cohort study (Voelz et aL, 1983) , 1987). Within the plutonium-exposed group, possible excesses for esophageal, stomach, colon, and prostate cancers were 11 also present at certain induction times.…”
mentioning
confidence: 99%